2022
DOI: 10.1002/mde.3718
|View full text |Cite
|
Sign up to set email alerts
|

Do private translation mechanisms encourage food safety in dairy production? Evidence from the Brazilian Conseleites

Abstract: This study investigates how and why the translation role of private meso‐institutions can help in the implementation of food safety norms in Brazilian dairy supply chains. Relying on a unique dataset containing producer‐level data, we combine a difference‐in‐differences approach with matching to investigate the experience of the Brazilian Conseleites. Our results indicate that milk quality levels tend to be higher in the states where Conseleites operate, suggesting a reduction in the cost of obtaining and diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Zhan et al [ 20 ] found the balance between quality improvement and cost consumption from the perspective of perishable food production process, and identified the key quality improvement links. De Oliveira et al [ 21 ] found that reducing the cost of accessing and disseminating information could improve the quality of milk products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhan et al [ 20 ] found the balance between quality improvement and cost consumption from the perspective of perishable food production process, and identified the key quality improvement links. De Oliveira et al [ 21 ] found that reducing the cost of accessing and disseminating information could improve the quality of milk products.…”
Section: Literature Reviewmentioning
confidence: 99%